Textures and Entanglements of Contemporary Afrikaner Cinema - Steenkamp, Emelia (Centre for Film and Media Studies, 2019)
During the apartheid era, white Afrikaner cinema largely served the purpose of placating, soothing, and bolstering the white middle class. Today, more than twenty years after the end of this regime, scholars are intrigued by the large amount of escapist, paradoxical, and ineffectual works still springing from the Afrikaner community. In this thesis I outline various vectors of ideological and cultural influence involved in Afrikanerdom, contemplating the seismic forces that have shaped cultural output. Then, following theories of Jacques Rancière and Achille Mbembe, I look at the aesthetic operations of Liefling (2010) and Pretville (2012), to inspect the insistence on 'cheer’ as part of the Afrikaner imagined community. In my subsequent chapter I conduct a close analysis of two dramatic films that do attempt engagement with South African realities, Krotoa (2017), and Sink (2015). In these texts, I nevertheless identify a signifying economy that abides by the same mythological structure as Liefling and Pretville. With these tendencies and contradictions in mind, I propose a potential artistic solution which I situate in a radically different strand of cinema—a cinema of affective intimacy exemplified in the work of Jenna Bass. Through such juxtaposition, and through identifying certain prevalent patterns, I ultimately find that the Afrikaner filmic milieu is deeply shaped by strata of history and power, and that it profoundly showcases the labyrinthine sociopolitics of South Africa